Ayah Di Mataku "Orientasi Seksual Menjadi Gay Ditinjau Dari Persepsi Terhadap Peran Ayah" - Matofani, Fani; , Aad Satria Permadi, S.Psi, MA (2017)
This research aims to understand the sexual orientation being gay in terms of perception of the role of the father. This research used the descriptive qualitative approach, collecting data using a semi structured interview techniques. Informants in this study is selected by purposive sampling, that amounted to 5 people, 3 people are gay and 2 people are heterosexual. From this research obtained the results that the closeness of the relationship of the child with a father who is entwined with no good will made a bad experience between them, when the experience of the child with a bad dad, with along a bad stories about the father from his mother, then it will cause a bad perception by the son against the father, it can influential for a child's response to the establishment of his identity. A Son did not find their ideal father in the figure of his father, then the son will be trying to find a father figure should ideally be from other people who are older. At the age of adolescence, at the son are free to interact with the environment, has many friends and a lot of experience with people, when a son accidentally gets a good experience with gay men, and find the ideal father of his partner , will cause a child addicted to repeat the behavior of gays who settled. Keyword : Father figure, Gay, Perception of father